Pharmacological interventions for preventing opioid-induced hyperalgesia in adults after opioid-based anesthesia: a systematic review and network meta-analysis - Xie, Wei-Ji; Hong, Ji-Shuang; Feng, Cheng-Fei; Chen, Hao-Feng; Li, Wei; Li, Yong-Chun (Frontiers in Pharmacology, 2023)
Abstract Background: Opioid-induced hyperalgesia (OIH) is an adverse event of prolonged opioid use that increases pain intensity. The optimal drug to prevent these adverse effects is still unknown. We aimed to conduct a network meta-analysis to compare different pharmacological interventions for preventing the increase in postoperative pain intensity caused by OIH. Methods: Several databases were searched independently for randomized controlled trials (RCTs) comparing various pharmacological interventions to prevent OIH. The primary outcomes were postoperative pain intensity at rest after 24 h and the incidence of postoperative nausea and vomiting (PONV). Secondary outcomes included pain threshold at 24 h after surgery, total morphine consumption over 24 h, time to first postoperative analgesic requirement, and shivering incidence. Results: In total, 33 RCTs with 1711 patients were identified. In terms of postoperative pain intensity, amantadine, magnesium sulphate, pregabalin, dexmedetomidine, ibuprofen, flurbiprofen plus dexmedetomidine, parecoxib, parecoxib plus dexmedetomidine, and S (+)-ketamine plus methadone were all associated with milder pain intensity than placebo, with amantadine being the most effective (SUCRA values = 96.2). Regarding PONV incidence, intervention with dexmedetomidine or flurbiprofen plus dexmedetomidine resulted in a lower incidence than placebo, with dexmedetomidine showing the best result (SUCRA values = 90.3). Conclusions: Amantadine was identified as the best in controlling postoperative pain intensity and non-inferior to placebo in the incidence of PONV. Dexmedetomidine was the only intervention that outperformed placebo in all indicators. Clinical trial registration: CRD42021225361 (PROSPERO).